SHÌ (是) DALAM BAHASA CINA MODERN (现代汉语) DAN KLASIK (古代汉语) - Yulie Neila Chandra (Bambuti, 2019)
Abstract. This article describes the use of the word 是(shi) in Modern Chinese Language (Mandarin/MCL) and Classical Chinese Language (CCL), and compares them so that can understand the similarities and differences of the word, both the structure (includes the class of words) and their meaning. This study describes the symptoms of language especially in syntactic and semantic, using comparative analysis methods. The results of analysis indicates that generally the word 是(shi) in MCL is verb, functions as a predicate, and becomes a connecting verb (copula) between the subject and its object, or connects nouns, pronouns, other phrases, and expresses many meanings. Conversely, the use of 是(shi) in CCL is very rare, and generally not as verbs or copula, but as pronouns and conjuctions.